USE OF INTERACTIVE METHODS IN INCREASING STUDENT ACTIVITY (British Journal of Global Ecology and Sustainable Development, 2024)
In this article, the author tried to express his opinions about the use of interactive methods to increase the activity of students in the current English and Uzbek languages. In this, the author's focus is on the use of interactive methods to increase the activity of students written in English and Uzbek as the main research material. In the process of preparing the article, the author critically approached the views of English and Uzbek linguists and boldly expressed his opinions. The article may be useful for those who study English and Uzbek translation studies and its lexicology.